Sustainable Auditing: Practices and Perceptions in the Accounting Industry - Nugroho, Hadi; Permata, Inggit (Manunggal Halim Jaya, 2023)
This study aims to explore sustainable auditing practices and perceptions within the accounting industry, focusing on organizational approaches, stakeholder engagement, and implications for future research and practice. A qualitative literature review was conducted to synthesize key findings from existing research. The research revealed a spectrum of sustainable auditing practices adopted by organizations, with large multinational corporations leading in adoption as part of their corporate social responsibility initiatives. However, small and medium-sized enterprises (SMEs) face challenges due to resource constraints and competing priorities. Tailored interventions such as capacity-building initiatives, collaborative partnerships, and simplified reporting frameworks are essential to facilitate sustainable auditing adoption among SMEs. Stakeholders' perceptions vary, with some viewing sustainable auditing positively for enhancing organizational performance and reputation, while others express skepticism about its effectiveness and relevance. Cultural factors influence stakeholders' attitudes, emphasizing the need for context-specific approaches to sustainable auditing. The study underscores the importance of stakeholder engagement, transparency, and capacity-building initiatives for organizations aiming to adopt sustainable auditing practices. Methodological challenges related to measuring and reporting sustainability performance must be addressed to enhance credibility and comparability. Future research should focus on understanding the mechanisms and outcomes of sustainable auditing and developing context-specific strategies to enhance its effectiveness.